Concurrent Cryptosporidium parvum outbreaks: molecular characterisation supporting epidemiological investigations leads to identification of different implicated food items, Sweden, 2019 - Jessica Beser (Eurosurveillance, 2025)
In Sweden, an increase in the number of notified cases of cryptosporidiosis was observed 1 October–31 December 2019 (462 domestic cases). Although a single national outbreak was initially suspected, molecular and epidemiological analyses revealed two concurrent national outbreaks and three local outbreaks. Cryptosporidium parvum subtype IIdA22G1c and IIdA24G1 were identified as the cause of the national outbreaks and subtype IIdA20G1e and IIdA21G1 as the cause of the local outbreaks. A case-case study comparing exposures in IIdA22G1c to IIdA24G1 revealed that cases with subtype IIdA22G1c (n = 48) were associated with consumption of a fresh fruit-and-vegetable juice (adjusted odds ratio (aOR) = 17; 95% confidence interval (CI): 1.8–169; p = 0.002). In the local outbreaks with subtype IIdA20G1e and IIdA21G1, cohort studies suggested that cases were associated with consumption of salads. Several coinciding outbreaks with different C. parvum subtypes explained the increase of cryptosporidiosis, and molecular typing was crucial in guiding relevant cross-disciplinary collaboration.